Higher Education Selection using Simple Additive Weighting - Aminudin, Nur; Huda, Miftachul; Kilani, Ahmad; Wan Embong, Wan Hassan; Mohamed, Ahmad Marzuki; Basiron, Bushrah; Ihwani, Siti Suhaila; Mohd Noor, Sulaiman Shakib; Jasmi, Kamarul Azmi; Safar, Jimaain; L. Ivanova, Natalie; Maseleno, Andino; et al. (International Journal of Engineering and Technology, 2018)
The process of selecting a college should be based on the capabilities and needs of the community. When society is faced with a large selection of college criteria and most societies are confused about choosing the appropriate college for themselves and the job demands. From this it was made a decision support system aimed at helping the community to choose a college that suits the ability and demands of the work. Decision support system plays a role in helping people get the right recommendations in the selection of universities. This decision support system is also designed to help the community to choose a college that suits their needs so that the public is not confused because of the many criteria of universities faced by the community because the admin already has recommendations according to the needs of the community by using Simple Additive Weighting (SAW) method.